Wolterstorff on Love and Justice. Issue 1 (27th January 2013) - Clair, Joseph
Abstract In Justice in Love, Nicholas Wolterstorff argues for a unique ethical orientation called "care‐agapism." He offers it as an alternative to theories of benevolence‐agapism found in Christian ethics on the one hand and to the philosophical orientations of egoism, utilitarianism, and eudaimonism on the other. The purported uniqueness and superiority of his theory lies in its ability to account for the conceptual compatibility of love and justice while also positively incorporating self‐love. Yet in attempting to articulate a "bestowed worth" account of human dignity—in which dignity is given by divine love and respected in acts of justice—Wolterstorff leans on an unstable characterization of how love and the good are conceptually interwoven. As a result, his reader cannot be sure about the theoretical superiority of care‐agapism. Moreover, Wolterstorff's attempt to value self‐love and at the same time reject eudaimonism depends on a dubious interpretation of Augustine carried over from Justice: Rights and Wrongs, which itself further depends on a mischaracterization of the possible varieties of eudaimonism. This mistake is unfortunate because, on a closer reading of Augustine, one finds an agapistic account of eudaimonism that could have significantly helped Wolterstorff's overall account of the complementary relation of love and justice.